Preparedness of Earthquake Disaster for Communities Koto Tangah Sub-District - Padang City (Case Study of Elementary School 31 Pasir Kandang) - Arman, Arman; Ganefri, Ganefri; Syah, Nurhasan (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
In the last five years, the west coast of Sumatra island has experienced several earthquakes with strong intensity. The Pariaman earthquake on September 30, 2009, as reported by USGS, was located on the west coast of Pariaman with a magnitude of 7.9 SR and MMI VII-VIII standard, with a depth of 80 km. has caused victims to humans and property which is quite large. The socialization carried out is in the form of presentations in the classroom. The material presented includes the definition of a disaster, types of disasters (natural, non-natural, and social disasters), disaster management (before a disaster, when a disaster occurs, after a disaster).